Security dilemma of a small state / Part One Sri Lanka in the South Asian Context - Jayasekera, P. V. J.; Institute for International Studies (Peradeniya, Sri Lanka) (New Delhi, India : South Asian Publishers ; Absecon Highlands, N.J., USA : Distributed in USA by International Book Co., 1992)
Research conducted by the Institute for International Studies, Peradeniya, Sri Lanka.
pt. 1. Sri Lanka in the South Asian context -- pt. 2. Internal crisis and external intervention in Sri Lanka.
Includes index.
Includes bibliographical references.
Keywords: National security -- Sri Lanka; Sri Lanka -- Politics and government -- 1978-; South Asia -- Politics and government